2012
DOI: 10.4187/respcare.01617
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Complications of Tracheal Reintubation in Critically Ill Adults

Abstract: Nearly 20% of critically ill patients required out of operating room reintubation. Reintubation was associated with higher mortality, stay, and cost. Moreover, a difficult airway at reintubation was associated with higher mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
1
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(71 citation statements)
references
References 19 publications
7
58
1
5
Order By: Relevance
“…Details of the study population have been previously reported. 5 Overall, the subjects were 49.5 Ϯ 17.9 years of age, 66% were male, and the mean SAPS II score was 39.4 Ϯ 15.2. Subjects who required reintubation any time during their ICU or hospital stay tended to be older and have a higher mean SAPS II.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Details of the study population have been previously reported. 5 Overall, the subjects were 49.5 Ϯ 17.9 years of age, 66% were male, and the mean SAPS II score was 39.4 Ϯ 15.2. Subjects who required reintubation any time during their ICU or hospital stay tended to be older and have a higher mean SAPS II.…”
Section: Resultsmentioning
confidence: 94%
“…A recent study at our institution examined fluid balance in patients with subarachnoid hemorrhage, and suggested extensive day-to-day variability in the response to fluid administration. 18 We defined early extubation failure as reintubation within 24 hours, as the median time to reintubation was 22 hours, 5 thereby capturing more than half of extubation failures within this window. Furthermore, 24 hours is an important post-extubation milestone in the decision to transfer a patient out of the ICU after liberation from mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Identifying the clinical characteristics that are predictors of reintubation is important for caregivers. As demonstrated by Smina and colleagues, 5 CPF is an independent predictor of reintubation.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Furthermore, re-intubation is associated with a 5-fold increase in the relative odds of death and a 2-fold increase in median ICU and hospital stay, as well as institutional costs. 11 Thus, avoiding reintubation is important.…”
Section: Introductionmentioning
confidence: 99%